Quality of life and growth hormone deficiency in adult patients in clinical evaluation and health economic assessment - Kołtowska-Häggström, Maria (Pediatric endocrinology, diabetes, and metabolism, 2009)
Quality of life (QoL) has emerged as a construct that has found applications across healthcare-related fields. In clinical applications QoL is evaluated within a certain disease in patient populations and in individual patients, whereas pharmacoeconomics requires that QoL is expressed as a single summary score (a health status index)--most often utility index, which is capable of quantifying differences between diseases. Impairment of QoL in hypopituitary adult patients without growth hormone (GH) replacement therapy has been evident for a long time. The benefits of GH, as assessed by randomized clinical trials, remain controversial with some studies showing benefits and others refuting them. One of the studies based on the KIMS (Pfizer International Metabolic Database), showed that irrespectively of the degree of initial impairment, overall QoL during long-term GH treatment, improved dramatically in the first 12 months, with steady progress thereafter towards the country-specific population mean. Problems with memory and tiredness were the most serious burden for untreated patients, followed by tenseness, self-confidence and problems with socialising. With treatment these improved in the reverse order, normalising for the latter three. Another KIMS study examined QoL, measured by utility-weighted index (QoL-AGHDA(utility)). QoL-AGHDA(utility) in patients before GH treatment differed from the population values. The main improvement occurred during the first year of treatment; however, the patients' utilities remained during subsequent follow-up, different from those reported by the general population. Despite an observed impact of age, aetiology, disease-onset and co-morbidities on QoL-AGHDA(utility), all patients showed similar beneficial response to treatment.